2009
DOI: 10.1016/j.ijporl.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Cysts

Abstract: With the advent of flexible and rigid fiber-optic technology and modern imaging techniques, and in particularly prenatal diagnostic techniques, nasopharyngeal cysts recognition is more common than previous times and requires an appropriate consideration. Familiarity with these lesions is essential for the pediatric otolaryngologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
20

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 60 publications
0
32
0
20
Order By: Relevance
“…They may also be acquired following adenoidectomy, nasopharyngitis and chemoradiation for nasopharyngeal carcinoma in adults. 1 These cysts are deep to the pharyngobasilar fascia. 6 The most common lateral nasopharyngeal cysts are branchiogenic cysts; mucus retention cysts can also arise from lateral aspect, but rarely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also be acquired following adenoidectomy, nasopharyngitis and chemoradiation for nasopharyngeal carcinoma in adults. 1 These cysts are deep to the pharyngobasilar fascia. 6 The most common lateral nasopharyngeal cysts are branchiogenic cysts; mucus retention cysts can also arise from lateral aspect, but rarely.…”
Section: Resultsmentioning
confidence: 99%
“…1 Asymptomatic cysts are not uncommon, but symptomatic cysts are relatively uncommon. Only a few studies in literature have reported about nasopharyngeal cysts which are symptomatic.…”
Section: How To Cite This Articlementioning
confidence: 99%
“…They are mostly asymptomatic and infrequently found during routine endoscopies and imaging studies. Rarely they maybe the source for unexplained sinonasal symptoms, such as CSF rhinorrhea, visual disturbances and nasal obstruction [7].…”
Section: Discussionmentioning
confidence: 99%
“…Large or superinfected cysts can present with symptoms such as nasal obstruction, post nasal drainage, halitosis, aural fullness, and diminished hearing secondary to eustachian tube obstruction [1,2]. Nasopharyngeal cysts may be divided into two types: congenital and acquired cysts.…”
mentioning
confidence: 99%
“…Symptomatic cysts can be diagnosed by endoscopic nasopharynx examination and radiological examinations, such as computed tomography (CT) scans and MRI. MR imaging is superior to CT scans for detecting nasopharyngeal cysts, because it provides excellent details of soft tissues and distinguishes the contents of cysts [2]. Small, asymptomatic cysts do not require surgical intervention.…”
mentioning
confidence: 99%